Themed issues on per- and polyfluoroalkyl substances. Issue 11 (16th October 2019) - Ahrens, Lutz; Benskin, Jonathan P.; Cousins, Ian T.; Crimi, Michelle; Higgins, Christopher P.
Abstract : Guest editors Lutz Ahrens, Jonathan Benskin, Ian Cousins, Michelle Crimi and Christopher Higgins introduce the "Per- and polyfluoroalkyl substances (PFASs)" themed issue.